2021
DOI: 10.1007/s40123-021-00435-1
|View full text |Cite
|
Sign up to set email alerts
|

A One-Week Course of Levofloxacin/Dexamethasone Eye Drops: A Review on a New Approach in Managing Patients After Cataract Surgery

Abstract: A new fixed-dose combination of dexamethasone and levofloxacin eye drops has recently been approved for the prevention and treatment of inflammation, and the prevention of infection associated with cataract surgery in adults. This combination has been developed to respond to a series of unmet needs in the practical management of patients undergoing cataract surgery. Namely, despite updated guidelines, many ophthalmologists employ protocols mainly based on their personal experience. As a result, the choice of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, it should be noted that some clinical trials indicate the efficacy of compounded preparations. Rizzo et al analyzed the effects of 1-week course of levofloxacin + dexamethasone eye drops in managing patients after cataract surgery [21]. The authors showed that the concentrations of both drugs at the site of action was high enough to prevent infection and inhibit the inflammatory process despite relatively short treatment duration.…”
Section: Opinion Of An Expert In Medical Microbiologymentioning
confidence: 99%
“…However, it should be noted that some clinical trials indicate the efficacy of compounded preparations. Rizzo et al analyzed the effects of 1-week course of levofloxacin + dexamethasone eye drops in managing patients after cataract surgery [21]. The authors showed that the concentrations of both drugs at the site of action was high enough to prevent infection and inhibit the inflammatory process despite relatively short treatment duration.…”
Section: Opinion Of An Expert In Medical Microbiologymentioning
confidence: 99%
“…Indeed, apart from instances of DEX being loaded into solid DDS like tablets or intravitreal implants [ 19 ], the most commonly used dosage forms currently available on the market are eye drops in which the drug is in suspension, either alone or in the presence of other active ingredients (e.g., levofloxacin, tobramycin, netilmicin). Formulations to date on the market have a 0.1% w/v of DEX, and the usual dose of DEX-based eye drops is one drop per eye repeated every 4 h. The administration of eye drops formulations is particularly challenging [ 20 ] due to the presence of static ocular barriers, such as anatomical (cornea, sclera, retina), haemato-aqueous, and haemato-retinal barriers. Moreover, the presence of dynamic barriers, such as the nasolacrimal duct, blinking reflex, and the low receiving volume of the conjunctival sac (20–50 µL), greatly reduce the bioavailability of drugs at the ocular AS [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of eye drops can represent an obstacle for these patients, given the difficulty in instilling the drops in multiple and repeated administrations at different times of the day. Thus, there is a need to formulate a safe, manageable, and effective product that can ensure the resolution of inflammation and optimal adherence to therapy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Introducing routine prophylactic antibiotics following cataract surgery has been associated with a significant decrease in endophthalmitis rates. Intracameral and topical antibiotics are currently utilized to prevent this condition, depending on the surgeon's preference and local resistance patterns ( 8 ).…”
Section: Introductionmentioning
confidence: 99%